GERAKAN MENANAM BIBIT MANGROVE (Rhizophora sp) SEBAGAI UPAYA REHABILITASI EKOSISTEM MANGROVE DI DESA KUALA BUBON ACEH BARAT - Neneng Marlian; Nabil Zurba; Mira Mauliza Rahmi; Fryuanita Lubis; Fitria Rahmayanti; Dewi Fithria (Universitas Teuku Umar, 2022)
Mangrove rehabilitation is an activity to restore damaged mangrove ecosystems into an ecosystem that functions as it should. The mangrove rehabilitation program is an ongoing program consisting of site surveys, outreach to the community, planting of mangrove seedlings, and post-planting maintenance of mangrove seedlings. This community service was carried out on February 20, 2022 in Kuala Bubon Village, West Aceh Regency. This activity was attended by the academic community of the Aquatic Resources Study Program and the local community who live in Kuala Bubon Village. The implementation of community service aimed to increase public and student awareness to preserve the mangrove ecosystem and restore degraded mangrove ecosystems through rehabilitation. The method used is the counseling methode and live demonstration in the field. The mangrove rehabilitation program carried out by the academic community of the Aquatic Resources Study Program through the mangrove rehabilitation program has had an effect on increasing public and student awareness in an effort to preserve the mangrove ecosystem and restore the function of the damaged mangrove ecosystem through replanting mangrove seedlings and maintaining post-planting mangrove seedlings.